Design studies on the ERL-FEL test facility at IHEP, Beijing - 王书鸿 王九庆 陈森玉 池云龙 王光伟 曹建社 刘圣广 高杰 翟纪元 刘渭滨 崔小昊 徐金强 周祖圣 李小平 陆辉华 肖琼 (Chinese physics C, 2012)
A proposed compact ERL test facility at IHEP, Beijing, is presented in this paper, and includes the design parameters, the essential lattice, and the key components features, such as the photocathode DC gun and the CW superconducting accelerating structures. Some important beam physics issues such as the space charge effect, the coherent synchrotron radiation （CSR） effect and the beam break-up （BBU） effect are briefly described with the simulation results.